Pathogen Recognition by CD4 Effectors Drives Key Effector and Most Memory Cell Generation Against Respiratory Virus - Devarajan, Priyadharshini; Jones, Michael C.; Kugler-Umana, Olivia; Vong, Allen M.; Xia, Jingya; Swain, Susan L. (Frontiers in Immunology, 2018)
Although much is known about the mechanisms by which pathogen recognition drives the initiation of T cell responses, including those to respiratory viruses, the role of pathogen recognition in fate decisions of T cells once they have become effectors remains poorly defined. Here, we review our recent studies that suggest that the generation of CD4 T cell memory is determined by recognition of virus at an effector “checkpoint.” We propose this is also true of more highly differentiated tissue-restricted effector cells, including cytotoxic “ThCTL” in the site of infection and TFH in secondary lymphoid organs. We point out that ThCTL are key contributors to direct viral clearance and TFH to effective Ab response, suggesting that the most protective immunity to influenza, and by analogy to other respiratory viruses, requires prolonged exposure to antigen and to infection-associated signals. We point out that many vaccines used today do not provide such prolonged signals and suggest this contributes to their limited effectiveness. We also discuss how aging impacts effective CD4 T cell responses and how new insights about the response of aged naive CD4 T cells and B cells might hold implications for effective vaccine design for both the young and aged against respiratory viruses.